Determination of some heavy metal levels in three freshwater fish in Keban Dam Lake (Turkey) for public consumption - Caglar, M.; Canpolat, O.; Selamoglu, Z. (Iranian Fisheries Science Research Inst-Ifsri, 2019)
[Abstract Not Available]
Keywords: Heavy metals; Accumulation; Cyprinus carpio; Squalius cephalus; Capoeta umbla; Muscle